Calcineurin Regulatory Subunit Calcium-Binding Domains Differentially Contribute to Calcineurin Signaling in Saccharomyces cerevisiae. Issue 3 (7th May 2018) - Connolly, Sean; Quasi-Woode, Devona; Waldron, Laura; Eberly, Christian; Waters, Kerri; Muller, Eric M; Kingsbury, Tami J
Abstract: The protein phosphatase calcineurin is central to Ca 2+ signaling pathways from yeast to humans. Full activation of calcineurin requires Ca 2+ binding to the regulatory subunit CNB, comprised of four Ca 2+ -binding EF hand domains, and recruitment of Ca 2+ -calmodulin. Here we report the consequences of disrupting Ca 2+ binding to individual Cnb1 EF hand domains on calcineurin function in Saccharomyces cerevisiae . Calcineurin activity was monitored via quantitation of the calcineurin-dependent reporter gene, CDRE -lacZ, and calcineurin-dependent growth under conditions of environmental stress. Mutation of EF2 dramatically reduced CDRE -lacZ expression and failed to support calcineurin-dependent growth. In contrast, Ca 2+ binding to EF4 was largely dispensable for calcineurin function. Mutation of EF1 and EF3 exerted intermediate phenotypes. Reduced activity of EF1, EF2, or EF3 mutant calcineurin was also observed in yeast lacking functional calmodulin and could not be rescued by expression of a truncated catalytic subunit lacking the C-terminal autoinhibitory domain either alone or in conjunction with the calmodulin binding and autoinhibitory segment domains. Ca 2+ binding to EF1, EF2, and EF3 in response to intracellular Ca 2+ signals therefore has functions in phosphatase activation beyond calmodulin recruitment and displacement of known autoinhibitory domains. Disruption of Ca 2+ binding to EF1, EF2, or EF3 reduced Ca 2+ responsiveness of calcineurin, but increased the sensitivity of calcineurin to immunophilin-immunosuppressant inhibition. Mutation of EF2 also increased the susceptibility of calcineurin to hydrogen peroxide inactivation. Our observations indicate that distinct Cnb1 EF hand domains differentially affect calcineurin function in vivo, and that EF4 is not essential despite conservation across taxa.